Phonological Changes of Minangkabaunese Language Spoken by Chinese Ethnic in Padang - Sherly Katrina Putri; Jufrizal Jufrizal (English Language and Literature, 2022)
This research was aimed at finding out the phonemic and phonetic changes in Minangkabaunese language spoken by Chinese ethnic living in Padang. The type of this research was descriptive qualitative research. The data of this research were the sounds of words of Minangkabaunese language produced by Chinese Ethnic living in Pondok Area in Padang that experience phonological changes. The instruments that were used were list of words composed of 400 Minangkabaunese words, recording tool, and writing equipment. The data were collected using four techniques: interview, recording, transcribing, and note taking. The data were analyzed qualitatively. Based on the results of data analysis, it was found that there are seven kinds of phonemic changes and two kinds of phonetic changes that occur in the Minangkabaunese language spoken by Chinese ethnic living in Padang. It is concluded that the phonemic and phonetic changes that occur in Minangkabau Pondok dialect indicate that Minangkabaunese language is spoken by another different ethnic group that lives in Padang.